Structural biology meets typography: using protein structures to inspire creative expression and connect diverse audiences - Martínez-Núñez, Leonora (Frontiers in Bioinformatics, 2025)
Proteins are complex molecular machines with specific structures that determine their function. Advances in structural bioinformatics and visualization have expanded access to molecular data, most notably through the Protein Data Bank (PDB). This perspective explores the intersection between structural biology and typography, integrating a protein alphabet with the 36 Days of Type design project. Using ChimeraX, Blender and Molecular Nodes, 3D molecular models were processed, stylized, and shared on social media under the #36daysoftype hashtag, which led to engagement across a diverse audience. This work was also presented at VIZBI 2024 conference and influenced the VIZBI 2025 conference logo design. This project frames the role of scientific illustration and visual arts in connecting disciplines, boosting public engagement, and encouraging interdisciplinary collaboration, while also inspiring future applications like biology-inspired typography to enhance scientific literacy.